Innate immune response in implant-associated infections: neutrophils against biofilms - Dapunt, Ulrike A.; Hänsch, Gertrud Maria; Arciola, Carla Renata (Materials, 2016)
Biofilm has been recognized as a well-protected form of living for bacteria, contributing to bacterial pathogenicity, particularly for opportunistic species. Biofilm-associated infections are marked by their persistence. Extensive research has been devoted to the formation and composition of biofilms. The immune response against biofilms remains rather unexplored, but there is the notion that bacteria within a biofilm are protected from host defences. Here we glance at the mechanisms by which neutrophils recognize and face biofilms in implant infections and discuss the implications of this interplay, as well as speculate on its significance.